(untitled) (Foro de Educacion, 2020)
From the beginning, Educational Psychology had the objective of procuring tools to enhance the development of the educational practice. In this way, it offered knowledge to improve the students’ learning but also to discriminate those who presented difficulties of accommodation to the rhythms established by the school institution. From a historical analysis, this work will demonstrate how this discipline, conditioned by the situation that allowed its origin in the late nineteenth century, participated strategically in the emergence of a knowledge that legitimized school practice and established new government circuits for childhood. Following this, the perspectives that began to criticize the original paradigm of the discipline from the middle of the 20th century will be examined, exposing a certain naturalized pattern of psychological knowledge production in the school environment and thus promoting a contextual model that will take into account the broad characteristics of the teaching and learning process. Finally, it will be concluded that, in spite of the theoretical strength that these orientations have managed to distribute, the proliferation of psychological diagnosis in the school classrooms during the last decades, although protected under the argument of smoothing the borders between normal education and special education, would seem not only to eclipse and diminish the possibilities of the contextual model, but also to shake the traditional school structure and bear consequences of extreme importance for the current configuration of educational practice.